Asuhan Keperawatan pada Pasien Hipertensi menggunakan Terapi Foot Hand Massage dengan Essensial Oil Lavender terhadap Penurunan Tekanan Darah - Nabila Ajeng Ningtias; Dewi Damayanti; Pujiarto Pujiarto (Ners Akademika, 2023)
Purpose: Hypertension or high blood pressure is a state of change in which blood pressure increases chronically.  In general, hypertension is a condition without symptoms, in which the pressure is abnormally high in the arteries.  Massage techniques have an impact on the smooth circulation of blood flow, balance the flow of energy in the body and relax muscle tension.  The aim of this study was to determine and analyze nursing care in hypertensive patients using foot hand massage therapy with lavender essential oil to reduce blood pressure in hypertensive patients in Puskesmas Pringsewu.  Method: This research method using the Applied Research method aims to apply, test and evaluate the ability of a theory, which is applied in solving practical problems. The research subjects were taken by 2 people who fit the inclusion criteria, namely patients with primary hypertension, and patients with mild hypertension.  and moderate.  The instrument in this study used measuring instruments in the form of a spigmomanometer and SOP for foot hand massage therapy.  Result: The results obtained before the foot hand massage therapy were Stage 2 Hypertension and after the foot hand massage therapy was carried out it decreased to Pre-Hypertension.  The conclusion of this study is that there is a significant change in reducing blood pressure in both respondents before and after foot hand massage therapy for 3 days of administration.